LYSOSOMAL ENZYMES IN CELLS INFECTED WITH CYTOPATHIC AND NON-CYTOPATHIC VIRUSES - Livio Mallucci; A. C. Allison (1965)
In chick embryo cells infected with fowl plague virus, an avian strain of influenza A which produces cytopathic effects, lysosomal enzymes were released from the particulate to the supernatant fraction of homogenates within 6 hours of infection. This change occurred in the presence of high concentrations of parafluorophenylalanine, suggesting that the changes were due to redistribution of preformed enzymes rather than to de novo protein synthesis. No such changes were observed when the Melbourne strain of influenza A virus multiplied in the same cell system without cytopathic effects. The possible role of lysosomal enzymes in virus uncoating and in the genesis of cytopathic effects is discussed.